Corporate hosts: the rise of professional management in the short-term rental industry - Cocola-Gant, Agustín (2021)
This paper explores the rise of short-term rental (STR) management companies and reveals the transition from a sharing economy activity to the consolidation of a professional industry hinging on what we call ‘corporate hosts’. By relying on interviews with companies operating in Lisbon and Porto, Portugal, we found: first, that a phenomenon of market concentration occurred in which individual hosts have outsourced the management of their properties to corporate hosts; second, that through the use of digital technology and vertical integration, corporate hosts are able to enhance the profitability of large portfolios of STRs; and, third, that corporate hosts imitate practices from the hotel industry, leading to the formation of a hybrid product in which the lines between hotels and STRs have blurred. We argue that corporate hosts constitute a new layer of intermediation that challenges the way we understand the STR industry and the overall functioning of this market.